Evaluation of PCR Based Assays for the Improvement of Proportion Estimation of Bacterial and Viral Pathogens in Diarrheal Surveillance - Guan, Hongxia; Zhang, Jingyun; Xiao, Yong; Sha, Dan; Ling, Xia; Kan, Biao (Frontiers in Microbiology, 2016)
Abstract Diarrhea can be caused by a variety of bacterial, viral and parasitic organisms. Laboratory diagnosis is essential in the pathogen-specific burden assessment. In the pathogen spectrum monitoring in the diarrheal surveillance, culture methods are commonly used for the bacterial pathogens’ detection whereas nucleic acid based amplification, the non-cultural methods are used for the viral pathogens. Different methodology may cause the inaccurate pathogen spectrum for the bacterial pathogens because of their different culture abilities with the different media, and for the comparison of bacterial vs. viral pathogens. The application of nucleic acid-based methods in the detection of viral and bacterial pathogens will likely increase the number of confirmed positive diagnoses, and will be comparable since all pathogens will be detected based on the same nucleic acid extracts from the same sample. In this study, bacterial pathogens, including diarrheagenic Escherichia coli (DEC), Salmonella spp., Shigella spp., Vibrio parahaemolyticus and V. cholerae, were detected in 334 diarrheal samples by PCR-based methods using nucleic acid extracted from stool samples and associated enrichment cultures. A protocol was established to facilitate the consistent identification of bacterial pathogens in diarrheal patients. Five common enteric viruses were also detected by RT-PCR, including rotavirus, sapovirus, norovirus (I and II), human astrovirus, and enteric adenovirus. Higher positive rates were found for the bacterial pathogens, showing the lower proportion estimation if only using culture methods. This application will improve the quality of bacterial diarrheagenic pathogen survey, providing more accurate information pertaining to the pathogen spectrum associated with finding of food safety problems and disease burden evaluation.